Effect of Feeding Duration of Increased Lysine and Energy Prior to Farrowing on Sow Performance and Colostrum Quality - K. M. Gourley; A. J. Swanson; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 467 sows were used in a study to evaluate the effect of feeding duration of increased lysine (Lys) and energy prior to farrowing on sow and litter performance, piglet survival, and colostrum quality. Sows were blocked by body weight and parity category on d 106 of gestation, and allotted to one of three dietary treatments: 1) 4.5 lb/d gestation feed (12.5 g SID Lys and 6.5 Mcal ME) until d 113 of gestation, then 6 lb/d lactation feed (28 g SID Lys and 9.4 Mcal ME) until parturition; 2) 4.5 lb/d gestation feed (12.5 g SID Lys and 6.5 Mcal ME) until d 113 of gestation, then 8.3 lb/d lactation feed (40 g SID Lys and 13.3 Mcal ME) until parturition; or 3) 8.3 lb/d lactation feed (40 g SID Lys and 13.3 Mcal ME) from d 107 of gestation until parturition. Data were analyzed for treatment within parity effects using the GLIMMIX procedure of SAS. Increasing the duration of feeding additional standardized ileal digestible (SID) Lys and energy increased (P<0.05) sow weight gain from d 106 to 113. Sow backfat gain from d 106 to 113 of gestation increased (P<0.05) in gilts and sows fed 8.3 lb/d of the lactation diet starting on d 107 vs. the control diet. There was no evidence (P>0.05) for difference in female body weight (BW) or backfat loss from d 113 of gestation until weaning between treatments. Average total born and born alive piglet birth weight was greater (P<0.05) in gilts fed 8.3 lb/d lactation diet starting on d 107 or 113 vs. control, with no evidence (P>0.05) for difference in average piglet birth weight in sows or weaning weight in gilts and sows. Piglet mortality after cross-foster to weaning was decreased (P<0.05) in sows fed 8.3 lb/d lactation diet starting on d 113 vs. control or increased lactation diet starting on d 107, but not in gilts. However, litter gain from 48 h to weaning was decreased (P<0.05) in gilts fed 8.3 lb/d lactation diet starting on d 107 compared to control, with no difference in sows. For colostrum composition, fat and total solids were decreased (P<0.05) in sows fed 8.3 lb/d of the lactation diet starting on d 107 compared to the control, with no difference observed in gilts. There was no evidence for difference (P>0.05) in colostrum protein or lactose concentration due to dietary treatment. Colostrum immunoglobulin G was increased (P<0.05) in gilts and sows fed 8.3 lb/d of the lactation diet starting on d 113 compared to control. Piglet colostrum intake and colostrum yield were not different (P>0.05) due to dietary treatment fed pre-farrow. For subsequent female performance, there was no evidence for difference (P>0.05) among treatments in the wean-to-estrus interval, percentage of females in estrus by d 7, farrowing rate, or subsequent litter characteristics. In summary, providing high Lys and energy intake from d 107 or 113 to farrowing increased piglet birth weight in gilts; however, litter gain to weaning was reduced when gilts started on high lactation feed intake at d 107 compared to gilts not fed increased Lys and energy. Providing high Lys and energy intake from d 113 increased pre-weaning piglet survival in sows. Colostrum intake and yield, and subsequent reproductive performance were unaffected by dietary treatments. In conclusion,ad libitumfeeding of a lactation diet when gilts are loaded into the farrowing house may be adequate to meet the additional Lys and energy requirements for fetal growth. However, further research is needed to determine why a reduced litter growth occurred in gilts fed increased Lys and energy prior to farrowing.
Keywords: transition sow; colostrum; lysine; energy